Oracle Database 12c PL/SQL programming : design and deploy powerful, database-centric PL/SQL applications - McLaughlin, Michael (McGraw-Hill Education, 2014)
"A complete update of the essential desktop reference for PL/SQL, rewritten and expanded by to highlight the massive changes in Oracle Database 12c. Written by an Oracle ACE, Oracle Database 12c PL/SQL Programming offers in-depth information on the entire PL/SQL language and its extensibility to develop applications. With full coverage of the latest features and tools, this Oracle Press guide provides examples of web applications in native PL/SQL, JSP, and PHP. The book explains how to access and modify database information, construct powerful PL/SQL statements, execute effective queries, and deploy security. A Netflix case study example is used throughout the book as the basis for all coding examples. This enables application design consideration, data types, structures, and coding approaches to build an integrated view of the PL/SQL programming language. The examples collectively provide you with both a reference to how various programming concepts work and how components fit together to solve real-world problems"--$cProvided by publisher.